Increasing Interspecific Difference of Alpine Herb Phenology on the Eastern Qinghai-Tibet Plateau - An, Shuai; Chen, Xiaoqiu; Shen, Miaogen; Zhang, Xiaoyang; Lang, Weiguang; Liu, Guohua (Frontiers in Plant Science, 2022)
The phenology of alpine grassland on the Qinghai-Tibet Plateau (QTP) is critical to regional climate change through climate-vegetation feedback. Though many studies have examined QTP vegetation dynamics and their climatic sensitivities, the interspecific difference in the phenology response to climate change between alpine species are poorly understood. Here, we used a 30-year (1989-2018) record of in-situ phenological observation for five typical alpine herbs (Elymus nutans, Kobresia pygmaea, Plantago asiatica, Puccinellia tenuiflora and Scirpus distigmaticus) and associated climatic records at Henan Station in the eastern QTP to examine the species-level difference in spring and autumn phenology and then quantify their climate sensitivities. Our results show that with significantly warming, the green-up dates of herbs were insignificantly shifted, while the brown-off dates in four out of the five herbs were significantly delayed. Meanwhile, the interspecific difference in brown-off dates significantly increased at a rate of 0.62 d/a from 1989 to 2016, which was 3 time larger than that in green-up dates (0.20 d/a). These diverse rates were attributed to the different climate controls on spring and autumn phenology. In particular, green-up dates in most of herbs were sensitive to mean surface temperature, while brown-off dates were sensitive to night surface temperature. Further, brown-off dates are less sensitive to the warming in high ecological niche (with higher herb height and aboveground biomass) herbs than low niche herbs (with lower herb height and aboveground biomass). The increased phenology interspecific difference highlights the complex responses of herbs to future climate change even under the same alpine environment and indicates a potential alternation in plants community of alpine QTP, which may further influence the regional climate-vegetation feedback.